2023
DOI: 10.3389/fmars.2023.1158947
|View full text |Cite
|
Sign up to set email alerts
|

Ramicrusta invasive alga causes mortality in Caribbean coral larvae

Abstract: The settlement of coral larvae is an important process which contributes to the success and longevity of coral reefs. Coral larvae often recruit to benthic structures covered with crustose coralline algae (CCA) which produce cues that promote settlement and metamorphosis. The Peysonneliaceae Ramicrusta spp. are red-brown encrusting alga that have recently become abundant on shallow Caribbean reefs, replacing CCA habitat, overgrowing corals and potentially threatening coral recruitment. In order to assess the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Homoserine betaine was detected at two reefs (JS and TK) and had a significant positive correlation to the encrusting red-brown algaeRamicrusta (Figure 4), an invasive species on coral reefs shown to overgrow corals and threaten coral recruitment. 60,61 Homoserine betaine is a novel metabolite structurally identified by Pade et al 2016 and previously reported in a green alga Monostroma nitidium, 62 shellfish Callista brevisiphonata, 63 and a turban shell Turbo argyrostoma. 62 Its specific function in reef and nonreef organisms is largely undescribed, excluding Pade et al 2016, where the novel role of homoserine betaine as a previously unknown, compatible solute produced by the cyanobacterium Trichodesmium spp.…”
Section: Relationship Between Reef Benthos and Dissolved Metabolitesmentioning
confidence: 86%
“…Homoserine betaine was detected at two reefs (JS and TK) and had a significant positive correlation to the encrusting red-brown algaeRamicrusta (Figure 4), an invasive species on coral reefs shown to overgrow corals and threaten coral recruitment. 60,61 Homoserine betaine is a novel metabolite structurally identified by Pade et al 2016 and previously reported in a green alga Monostroma nitidium, 62 shellfish Callista brevisiphonata, 63 and a turban shell Turbo argyrostoma. 62 Its specific function in reef and nonreef organisms is largely undescribed, excluding Pade et al 2016, where the novel role of homoserine betaine as a previously unknown, compatible solute produced by the cyanobacterium Trichodesmium spp.…”
Section: Relationship Between Reef Benthos and Dissolved Metabolitesmentioning
confidence: 86%
“…In the years since Lillis’ data were collected in 2017, Tektite Reef has faced numerous acute and chronic stressors including a major bleaching event and the previously mentioned SCTLD outbreak which has led to the rapid mortality of several massive coral species [ 54 , 55 ]. Our own surveys of Tektite have noted decreases in hard coral cover from 28.9% in 2017 to 19.8% in 2022 with concurrent increases in the presence of cyanobacterial mats and macroalgae (TA Mooney 2017–2022, unpublished data), including overgrowth of peyssonnelid algal crusts which threaten natural larval settlement [ 56 ]. Although we did not note major differences in the overall shapes of acoustic spectra recorded at Tektite and Cocoloba in 2022 compared with 2017 ( figure 5 a ; electronic supplementary material, figure S2), Kaplan & Mooney [ 43 ] reported that hourly SPL RMS levels in the low-frequency (100–1000 Hz) band at Tektite in 2013 ranged from 100 to 105 dB re 1 μPa.…”
Section: Discussionmentioning
confidence: 99%
“…53 Homoserine betaine was detected at two reefs (JS and TK) and had a significant positive correlation to encrusting red-brown algae Ramicrusta (Figure 5), an invasive species on coral reefs shown to overgrow corals and threaten coral recruitment. 54,55 The presence and relatively high median concentrations of homoserine betaine at JS (1.6 nM) and TK (1.1 nM) is an intriguing finding that requires further investigation due to the limited information available regarding the potential function and presence of homoserine betaine in reef-associated organisms. GABA is a non-protein amino acid and one of the major inhibitory neurotransmitters in animal central nervous systems.…”
Section: Relationship Between Reef Benthos and Dissolved Metabolitesmentioning
confidence: 99%